Power fuzzy adaptive control for wind turbine - Yacine Hocini; Ahmed Allali; Houari Merabet Boulouiha (International Journal of Electrical and Computer Engineering (IJECE), 2020)
In recent years, wind energy has become one of the most promising renewable energy sources. The doubly-fed induction generator (DFIG) is currently the most common type of generator used in wind farms. This paper describes an approach for the independent control of the active and reactive power of the variable-speed DFIG. This paper deals with the control of the active and reactive powers in a DFIG designed for a wind system. The simulation model including a 7 KW - DFIG driven by a wind turbine, a PWM inverter and the proposed control strategy are developed and implemented using Matlab Simulink.